A novel method of shock wave induced seed germination and physiological growth of Catharanthus roseus. (2021) - Ramesh, R.; Sathiyanarayanan, P.; Lakshmi, D.; Sivakumar, A.; Martin Britto Dhas, S.A.; Liakath Ali Khan, F.
Abstract: We report a novel method of stimulating seed germination and plant growth using shock waves produced from the manually operated shock tube. The investigation was carried for the stimulation of seed germination and physiological growth of Catharanthus roseus . Seeds of Catharanthus roseus was sterilized in direct sunlight and shock waves are applied to the seeds with different Mach number (say 1.5MN, 1.7MN & 2.2MN) with the different number of shocks (5, 10 &15). For the systematic investigation, the experimental soil and the water used for the irrigation was tested for its compounds, pH and other physical and chemical properties. Physiological growths including plant height, number of leaves, shoot length were measured using POT studies. After 100 days of the growth period, the plant samples were harvested and dried in shadow. The phytochemical and biochemical screening was performed. Reports obtained from the POT analysis, calculated germination parameters proved that the application of shock waves to the seeds enhanced the germination rate and promoted plant growth in an considerable way.